Calidad de vida relacionada con la salud en un grupo de adolescentes de Medellín (Colombia): asociación con aspectos sociodemográficos, exceso de peso u obesidad y actividad física (2014)
ABSTRACT: The objective of the study was to describe health-related quality of life (HRQOL) and its association with socio-demographic aspects, overweight or obe- sity, and physical activity (PA) in a group of adolescents from the city of Medellín (Colombia). Different instruments were used in order to evaluate these variables in 399 participants. The HRQOL dimensions with the highest scores were Social Support and Friends and Mood and Feelings. Male primary school students with college-educated parents, be-longing to a high socio-economic level, engaging in high levels of PA, and without obesity caused by fat percentage or abdominal perimeter proved to have a better HRQOL.